Study of Compliance of Medical Records Officers with Medical Record Security and Confidentiality Regulations Regional General Hospital dr. Gondo Suwarno Semarang Regency - Windari, Adhani; Lestari, Sri; Fadhilah, Isnaini Qoriatul (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Regional General Hospital (RSUD) dr. Gondo Suwarno has implemented policies/regulations to maintain the security and confidentiality of medical records as outlined in several Standard Operating Procedures (SPO). Implementation of services often do not comply with these regulations, for several reasons. The purpose of this study is to find out the reasons/causes of these problems by carrying out research on Compliance with Security Regulations and Confidentiality of Hospital Medical Records in Semarang Regency. Subjects and Method: This type of qualitative descriptive research used a case study approach with observation and interview techniques conducted at Semarang District Hospital in January - April 2022. A total of 5 informants were selected in this study. Data were collected using interview guidelines and observation guidelines. Data is presented descriptively. Results: The result is dr. Gondo Suwarno already has an SPO to maintain the security and confidentiality of medical records, the procedures of which are in accordance with applicable health minister regulations. Characteristics of medical record officers 86% have Diploma Three in Medical Records and Health Information (D3 RMIK) education, 57% have worked for 25 years or more, and 71% are 50 years old or more. Officers have not fully complied with regulations to maintain the security and confidentiality of medical records, because they are constrained by policy support facilities that have not been fulfilled. Supporting facilities for medical record security and confidentiality policies are not fully available, such as document carrying bags and medical record storage rooms that do not have doors. Conclusion: SPO for maintaining the security and confidentiality of medical records whose procedures are in accordance with the applicable minister of health regulations, but officers have not fully complied with the regulations for maintaining the security and confidentiality of medical records, due to constraints on supporting policy facilities that have not been fulfilled. Keywords: compliance, regulation, security, confidentiality. Correspondence: Adhani Windari. Poltekkes Kemenkes Semarang. Pedalangan, Banyumanik, Kota Semarang, 50268 Jawa Tengah. Email: adhaniwindari@students.undip.ac.id. Mobile: +62 817-0582-584.